Identifying and resisting the technological drift: green space, blue space and ecotherapy - Ed Lord (Social Theory & Health, 2021)
There has been a growing interest in recent years into the health and well-being benefits of natural ‘green’ and ‘blue’ spaces. This theoretical paper presents a critical review of the proposed ways to operationalise these benefits for mental health. Following the social theories of Ellul and Bohme—in which technology is defined as a system of rules and rationality rather than devices and hardware—we propose that a process of ‘technological drift’ occurs when a body of evidence is put into practice in human activities (operationalised). We identify a technological colonisation of nature, in which nature itself is assimilated into a technological niche to act as a ‘technical solution to a technical problem’. Examples of this are the use of medical language like ‘dose’ and ‘prescription’, the attempt to separate effect mechanisms and pathways and the professionalisation and division of labour. Technological drift in nature exposure and health is congruent with a wider efficiency culture that reduces nature to a resource for human use. In conclusion, we propose that nature exposure could be not just an adjunct to healthcare systems but also disruptive to them in a positive and emancipatory way.